COMMUNICATIVE FUNCTIONS OF THE INTERJECTION - Mamushkina, S.Y (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
This article considers six pragmatic functions to a certain degree characteristic of English interjections. The emotive function in its pure form is more often performed by an interjection as a parenthesis in a sentence. The referential function is characteristic of the semantic group of interjections with a fixed meaning, while those with the definite invariant meaning of evaluation perform the evaluative function within the referential one. The phatic function is performed by some emotionally evaluative interjections when they are used to keep up a verbal contact. The conative function is characteristic of a number of interjections the main meaning of which is to express will. The poetic function as a special stylistic colouring is inherent in non-derivative interjections-vocatives on the invariant level. A sender uses them to give his message a special elevated form. The expressive function is realized in any use of the interjection and connected with a formal side of the utterance rather than its content. Among the linguistic means similar in their semantic meaning the author chooses interjections because of their higher expressiveness. A writer depicts his character more brightly and vividly and a reader gets the author's idea more adequately.